A comprehensive physico-chemical study on the molecular structure effects of sulfonated polyamide thin-film composites. Issue 1 (10th November 2016) - Hu, Jiahui; Liu, Yang; Cao, Xingzhong; Zhang, Peng; Zheng, Junfeng; Li, Meng; Zhang, Xuan; Wang, Lianjun
Abstract : Two similar monomers, 4, 4′-diaminodiphenyl ether-2, 2′-disulfonic acid (ODADS) and benzidine-2, 2′-disulfonic acid (BDSA), were used for the fabrication of the corresponding sulfonated thin-film composite (TFC) membranes with trimesoyl chloride (TMC) on the polysulfone substrate. Abstract : Two similar monomers, 4, 4′-diaminodiphenyl ether-2, 2′-disulfonic acid (ODADS) and benzidine-2, 2′-disulfonic acid (BDSA), were selected and used for the fabrication of the corresponding sulfonated thin-film composite (TFC) membranes with trimesoyl chloride (TMC) on the polysulfone substrate via conventional interfacial polymerization. Despite only a slight difference in the chemical structures of these two monomers, the as-prepared membranes exhibited distinctly different separation behaviors during the water desalination process. In brief, the molecular architectures significantly affected the solubility and the diffusion of the small molecules into the organic phase during the IP process. As a result, the corresponding barrier layers of TFC membranes were produced with different densities and thicknesses. Compared to TFC-BDSA, the TFC-ODADS membrane showed relatively lower water permeability but better rejection ability for ions, as confirmed by positron annihilation spectroscopy (PAS). By a dissipative particle dynamics (DPD) simulation approach, it was found that the molecular orientations of the active layer of the two membranes were in opposite directions. Specifically, the sulfonic acid groups in TFC-ODADS membrane surface were mostly facing outward, whereas they were enclosed by the hydrophobic polyamide backbone in the case of the TFC-BDSA membrane. As a consequence, the surface hydrophilicity was greatly enhanced for the former, as indicated by its higher water flux recovery ratio (FRR) of 96.8% for organic pollutants, which was much higher than that of the latter (81.8%).